EDUCO/United States Forest Service Lonetree - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2002)
Located in: Fort Collins office files. Letter from Gailmarie Kimmel of Interior West Center (IWC) Program Services discussing research on marketable uses of small diameter trees to make piece-on-piece wall panels with a supporting business card and three information sheets: Small diameter wood (SDW) in the construction industry, Using forest thinnings to introduce a different wall panelization system into log building construction; and Small log building seeks permanent home.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado